MICROFOSSILS FROM CHERTS OF THE MIDDLE RIPHEAN SVETLYI FORMATION, THE UCHUR-MAYA REGION OF SIBERIA, AND THEIR STRATIGRAPHIC SIGNIFICANCE - Sergeev V.N.; Seong-Joo L. (My University, 2001)
Silicided microfossils from the Middle Riphean Svetlyi Formation of the Riphean hypostratotype in the Uchur-Maya region of southeastern Siberia are described for the first time. Cherts are discovered to enclose only simple filamentous and coccoidal microorganisms: hollow sheaths of four hormogonian cyanobacteria species of the Siphonophycus genus (S. robustum, S. typicum, S. kestron, and S. solidum), filaments of the oscillatorian cyanobacteria Palaeolyngbya catenata, and spheroidal microfossils Myxococcoides sp. of the unclear taxonomic affinity. The Svetlyi microbiota differs from most assemblages of Middle-Late Riphean (Mesoproterozoic) age by the lack of ellipsoidal representatives of the Archaeoellipsoides genus. The low taxonomic diversity of silicified microfossils from the Svetlyi Formation and their organic-walled analogues from the underlying Lower Riphean Omakhta Formation suggest that the successive microfossil assemblages in the section of the Uchur-Maya Region cannot represent a standard for the entire Riphean succession. Description of microfossils from cherts of the Svetlyi Formation is presented.
Keywords: Riphean; Svetlyi Formation; Uchur-Maya region; Siberia; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей